Tolerant Saline Forage: Characteristic, Nutrient Content, Productivity and Cultivation - Harmini Harmini; Achmad Fanindi; Maureen Chrisye Hadiatry (Indonesian Center for Animal Research and Development, 2022)
The area of saline land in Indonesia will continue to expand which are potential to be used for forage development. The usage of saline land has a limiting factor of high salt content, that affects the productivity and nutritional quality forage. Several saline-tolerant fodder plants, including Pennisetum notatum, Pennisetum hybrida, Pennisetum purpureum, Panicum maximum, Setaria sphacelata, and Cynodon plectostachyus, have the potential to be developed. Plants respond to salinity by decreasing morphological performance, transpiration, and stomata. The productivity and nutrient content of grass are influenced by salinity. Saline-tolerant forage have similar productivity and nutrient content to those grown on optimal land. Fertilization, soil media, and the use of saline tolerant varieties can all be used to grow saline tolerant grass.